AI-Based Assistance System for Manufacturing - Deppe, Sahar; Brandt, Lukas; Brünninghaus, Marc; Papenkordt, Jörg; Heindorf, Stefan; Tschirner-Vinke, Gudrun
Manufacturing companies are challenged to make the increasingly complex work processes equally manageable for all employees to prevent an impending loss of competence. In this contribution, an intelligent assistance system is proposed enabling employees to help themselves in the workplace and provide them with competence-related support. This results in increasing the short- and long-term efficiency of problem solving in companies.
Keywords: Assistance system; Knowledge graph; Information retrieval; Neural networks; AR

AI-Based Assistance System for Manufacturing - Deppe, Sahar; Brandt, Lukas; Brunninghaus, Marc; Papenkordt, Jörg; Heindorf, Stefan; Tschirner-Vinke, Gudrun (2022 IEEE 27th International Conference on Emerging Technologies and Factory Automation (ETFA))

Determinants of Trust in Smart Technologies - Papenkordt, Jörg; Thommes, Kirsten (Human-Technology Interaction)

Same Different but not Same Same: Ethnic Discrimination in Application Procedures in the German Public Sector - Auer, Thorsten Fabian; Ekemen, Helin; Hagedorn, Carolin; Heise, Chantal; Rese, Christine (Empirical Economics Letters)
Regulations to prevent ethnic discrimination in accessing the labor market are implemented most thoroughly in the public sector. However, it remains to be assessed if these regulations are internalized. We conducted a field experiment to examine ethnic discrimination when applying for internships in German municipalities by unsolicited inquiries. We compared responses in German cities to Turkish, Italian, and German applicants in two periods, and find consistent disadvantages for the Turkish and Italian applicants as well as differences related to gender. Thus, the likelihood for ethnic discrimination rises when applying for positions in public institutions that are not subject to regulations.
Keywords: Ethnic Discrimination; Public Sector; Field Experiment; Application Procedure

Betriebliche Gesundheitsförderung: Ein leeres Versprechen? - Auer, Thorsten Fabian; Sennefelder, Lisa; Meier, Heiko (Public Health Forum)
Unternehmen investieren zunehmend in Angebote Betrieblicher Gesundheitsförderung (BGF). Dabei stellt sich die Frage nach dem Kosten-Nutzen-Verhältnis jenseits des individuellen Nutzens durch die Förderung der Mitarbeitergesundheit. Deshalb wurden im Rahmen einer Sekundäranalyse Effekte der BGF auf den Unternehmenserfolg berechnet. Die Ergebnisse lassen vermuten, dass sich eine verhaltensorientierte BGF kaum positiv auf die Arbeitsproduktivität und Kommunikationsstruktur in Unternehmen auswirkt.
Keywords: Kommunikation; Arbeitsproduktivität; Betriebliche Gesundheitsförderung; Kosten-Nutzen-Verhältnis

Künstliche Intelligenz in der industriellen Arbeitswelt - Papenkordt, Jörg; Gabriel, Stefan; Thommes, Kirsten; Dumitrescu, Roman
Im Rahmen dieser Studie wird der Status Quo des KI-Einsatzes in der industriellen Arbeitswelt in der Region OstWestfalenLippe erfasst und beschrieben. Dadurch wird eine Grundlage geschaffen, um eine zielführende Unterstützung der Gestaltung von durch Künstliche Intelligenz (KI) gestützter Arbeitsprozesse in Unternehmen zu ermöglichen, indem beispielsweise bedarfsbezogene Maßnahmen entwickelt und durchgeführt sowie weiterer Forschungsbedarf aufgezeigt wird. Die Befragung wurde im Jahr 2021 von dem Kompetenzzentrum Arbeitswelt.Plus sowie dem Spitzencluster it’s OWL initiiert. Dabei sind drei Zielgruppen – Unternehmensleitung, Personalabteilung (HR) sowie Arbeitnehmer*innen – adressiert worden. Insgesamt nahmen 317 Personen aus 89 verschiedenen Unternehmen bzw. Organisationen an der Befragung teil – zu 38 % Unternehmer*innen, zu 13 % Personaler*innen und zu 49 % Arbeitnehmer*innen. Die meisten der Teilnehmenden stammten aus der Elektroindustrie, dem Maschinenbau sowie dem Informations- und Kommunikationstechnologie (IKT)-Sektor. Die Befragungsergebnisse zeigen, dass sich die meisten Unternehmen in der Anfangsphase der KI-Nutzung befinden. Zwischen einzelnen Unternehmensbereichen und verschiedenen Branchen zeigen sich gewisse Unterschiede in der Nutzungsphase. Die Befragten stehen aktuell vor der Nutzung von vor allem teilautonomen KI-Systemen, die ausführende und analytische menschliche Tätigkeitenbeispielsweise durch Informationsbereitstellungen unterstützen. Wesentliche Ziele der KI-Nutzung sind die Effizienzsteigerung, Qualitätsverbesserung, Entscheidungsoptimierung sowie Unterstützung der Arbeitnehmer*innen. Allerdings werden in allen Unternehmen die fehlende Expertise sowie insgesamt die Komplexität des Themenfelds als Hinderungsgründe identifiziert. In allen Unternehmen und allen Unternehmensbereichen werden hohe Auswirkungen durch KI erwartet. Auf die Arbeitsgestaltung werden insgesamt eher positive Auswirkungen erwartet. Die Befragten schätzen die Bedeutung von KI, ihre Aufgeschlossenheit sowie ihr Vertrauen gegenüber KI als insgesamt hoch ein, ihr Verständnis von KI dagegen eher als gering. Tendenziell zeigt sich eine große Diskrepanz zwischen Selbst- und Fremdbild mit einer teils deutlich negativeren Wahrnehmung anderer. Die Befragten erwarten außerdem steigende Kompetenzanforderungen sowie einen hohen Weiterbildungsbedarf, insbesondere bezüglich des grundlegenden Verständnisses über KI. In den wenigsten Unternehmen existiert jedoch ein gezieltes Weiterbildungsangebot. Die Erkenntnisse aus der Befragung fließen im Rahmen des Kompetenzzentrums Arbeitswelt.Plus in die gezielte Gestaltung und Einführung KI-gestützter Arbeitsformen sowie bedarfsgerechter Unterstützungsangebote ein. Die hohe Komplexität der KI-Einführung sowie die sowohl technischen als auch mitarbeiterbezogenen Herausforderungen verdeutlichen den Bedarf für eine soziotechnische Perspektive und ein systematisches Vorgehen bei der Gestaltung dieses vielschichtigen Themenfelds.

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Since Albert and Whetten: the dissemination of Albert and Whetten’s conceptualization of organizational identity - Knorr, Karin; Hein-Pensel, Franziska (Management Review Quarterly)
Abstract Since the seminal work of Albert and Whetten, the organizational identity concept has become ubiquitous and highly relevant in various fields. This study systematically reviews how Albert and Whetten’s concept of organizational identity has been disseminated in different research areas. It employs quantitative (topic modeling) and qualitative text analysis, as well as a network analysis to examine a sample of 1,041 papers published between 1985 and mid-2022 that cite Albert and Whetten’s seminal work. Using this method of systematic literature analysis, the current study investigates the criteria of the basic definition and hypotheses mentioned in their work that contribute to its increasing significance, and those with the potential to become substantial aspects of future organizational identity research. Accordingly, Albert and Whetten’s conceptualization of organizational identity is often partially adopted in the literature. Thus, this study contributes to organizational identity research by unveiling further research questions on the evolving character of organizational identity, research methodology, and quantitative operationalization, on the basis of Albert and Whetten’s organizational identity conceptualization.
Keywords: Strategy and Management; Business; Management and Accounting (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia A.; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Can digital feedback increase employee performance and energy efficiency in firms? Evidence from a field experiment - Hoffmann, Christin; Thommes, Kirsten (Journal of Economic Behavior & Organization)

Decisions on Extending Group Membership—Evidence from a Public Good Experiment - Grund, Christian; Harbring, Christine; Thommes, Kirsten; Tilkes, Katja Rebecca (Games)
We experimentally compare the consequences for group cooperation of two decision mechanisms involving the extension of group membership. We analyze an exogenous decision (random draw) and an endogenous decision (made by a particular group member) mechanism to extend a temporary agent’s group membership. Our results reveal that the prospect of group membership extension affects not only the temporary but also the permanent group members’ contributions with an endogenous mechanism.

Is Corruption Imprinted? A Study on Preconditions of Corruption in Post-Communist Countries - Knorr, Karin; Auer, Thorsten Fabian; Thommes, Kirsten (Academy of Management Proceedings)

Der Einfluss von gesundheitsförderlichen Maßnahmen auf die Kommunikationsstrukturen: Nutzen für die Arbeitsproduktivität? - Meier, Heiko; Auer, Thorsten Fabian; Sennefelder, Lisa (Journal Gesundheitsförderung für Akteurinnen und Akteure aus Politik, Wissenschaft und Praxis)

Improved Knowledge Changes the Mindset: Older Adults’ Perceptions of Care Robots - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helinä; Gustafsson, Christine (HCII 2019)
This paper explores Finnish, German and Swedish older adults’ perceptions of a future welfare service with increased use of welfare technologies, specifically care robots. The issues are the rapid digitalization and development of health and welfare technology, which presently is mainly technology driven (not need or user driven), and the demographic challenge. The aim of the study was to explore older adults’ perception of the future use of welfare technology or care robots. A qualitative approach with focus group discussions was employed, followed by thematic analysis. The results are presented in four overall themes: the impact on daily life for older adults and professional caregivers, codes of practice and terms of use, dissemination of information and knowledge, and conditions for successful implementation. There were significant differences in the informants’ attitudes toward and knowledge about care robots. However, the informants’ attitudes appeared to change during the focus groups and in general, became more positive. Authentic needs, which care robots could support, refer to independence, safety and security, and the ability to manage or ease daily life or working life. The results suggest that older adults, after receiving relevant information, were open to the idea of being supported by care robots in their daily lives.
Keywords: Care robots; Older adults; Implementation; Information; Perceptions; Welfare technology

Group (Re-) formation in public good games: The tale of the bad apple? - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Journal of Economic Behavior & Organization)

Clean up your network: how a strike changed the social networks of a working team - Thommes, Kirsten; Akkerman, Agnes (Team Performance Management: An International Journal)

History as a source of organizational identity creation - Oertel, Simon; Thommes, Kirsten (Organization Studies)
We analysed the self-representation of twelve watchmaking firms located in a cluster in East Germany to understand how they apply rhetorical history to craft their identity. The findings show that there are common elements of rhetorical history that help organizations craft their identity, but there are also differences based on each firm’s historical background. While some firms specifically relate their identity to their own history, others mainly employ cluster-level history, while still others may even self-construct fictional historical roots. By discussing these findings, we contribute to a better understanding of how an organization’s identity is crafted and how history is utilized in such identity creation.

The Role of Contract Types for Employees’ Public Service Motivation - Grund, Christian; Thommes, Kirsten (Schmalenbach Business Review)

Age diversity and its effects on team performance - Klabuhn, Janny; Thommes, Kirsten (Academy of Management Proceedings)

Peer influence on protest participation: Communication and trust between co-workers as inhibitors or facilitators of mobilization - Born, Marieke; Akkerman, Agnes; Thommes, Kirsten (Social science research)

Elements of Organizational Identity and the Role of a Firm’s History - Thommes, Kirsten; Oertel, Simon (Academy of Management Proceedings)

Entrepreneurial activity-The impact of childhood - Thommes, Kirsten (Academy of Management Proceedings)

Shadows of the past: The effect of communist heritage on employee consultation - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (ILR Review)

Organizational Failure in the Aftermath of Institutional Upheaval - Thommes, Kirsten; Oertel, Simon; Walgenbach, Peter (Organization Studies)

Die Wirkungen des Outsourcings von Personalfunktionen – ein Überblick über verschiedene theoretische Ansätze und Entwicklung eines umfassenden Wirkungssets/ Effects of the outsourcing of personnel functions – an overview of several theoretical approaches and development of a comprehensive set of effects - Alewell, Dorothea; Bähring, Katrin; Thommes, Kirsten (Arbeit)
Abstract Unternehmen, die über das Outsourcing von Personalfunktionen entscheiden, stehen vor einer komplexen Fragestellung, da mit dem Bezug extern erbrachter Personaldienstleistungen sehr unterschiedliche Wirkungen ausgelöst werden können. Diverse Theorieansätze machen Aussagen zu einzelnen Wirkungskategorien des Outsourcings. Jedoch gibt bisher kein Ansatz dem Entscheidungsträger in der Praxis eine umfassende Entscheidungshilfe. Hier setzt der vorliegende Artikel an: Aus Ansätzen zur zwischenbetrieblichen Arbeitsteilung wird ein umfassendes „Wirkungsset“ des Outsourcings von Personalfunktionen hergeleitet, welches sich als Checkliste relevanter Wirkungskategorien eignet und die Einseitigkeiten bisheriger Ansätze vermeidet.
Keywords: Industrial and Manufacturing Engineering

Public good provision in blended groups of partners and strangers - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Economics Letters)

Behavioral spillovers from freeriding in multilevel interactions - Thommes, Kirsten; Vyrastekova, Jana; Akkerman, Agnes (Journal of Behavioral and Experimental Economics)

History as a Source of Competitive Advantages - Thommes, Kirsten; Oertel, Simon (Scandinavian Management Journal)

The internal market and the consumer: what consumers actually choose - Thommes, Kirsten; Faure, Michael; Heine, Klaus (Colum. J. Eur. L.)

The dark side of solidarity: social norms and social relations in the aftermath of strikes - Thommes, Kirsten; Akkerman, Agnes; Torenvlied, René; Born, Marieke (Industrial relations journal)

Contagious conflict: spill-over effects of labor conflict between and within organizations - Akkerman, Agnes; Torenvlied, René; Lehr, Alex; Thommes, Kirsten (Social conflict within and between groups)

Die Rechte von Arbeitnehmervertretern in Ost- und Westeuropa - Einheitseuropa oder Zweiklassengesellschaft? - Thommes, Kirsten; Walgenbach, Peter; Oertel, Simon

Born in the GDR: Imprinting, Structural Inertia and the Survival Chances of Organizations - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (Academy of Management Proceedings)

The after effects of strikes on team collaboration-experimental evidence - Thommes, Kirsten; Akkerman, Agnes; Vyrastekova, Jana (Academy of Management Proceedings)

HRM and the use of personnel services: an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Weiland, Katrin; Thommes, Kirsten (International journal of manpower)

HR outsourcing and service quality: theoretical framework and empirical evidence - Braun, Irene; Pull, Kerstin; Alewell, Dorothea; Störmer, Susi; Thommes, Kirsten (Personnel Review)

Explanatory factors for firms’ use of temporary agency work in Germany - Thommes, Kirsten; Weiland, Katrin (European Management Journal)

Triggers of HR outsourcing decisions--an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Thommes, Kirsten; Weiland, Katrin (The International Journal of Human Resource Management)

Wer nutzt HR-Outsourcing? Zentrale Strukturvariablen und ihr Einfluss auf die Nachfrage nach Personaldienstleistungen - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (German Journal of Human Resource Management)

Methodologische Grundlagen und Besonderheiten der qualitativen Befragung von Experten in Unternehmen: Ein Leitfaden - Bähring, Katrin; Hauff, Sven; Sossdorf, Maik; Thommes, Kirsten (Die Unternehmung schweizerische Zeitschrift für Betriebswirtschaft)

Verfügungsrechte über Humanvermögen: Implikationen für und Möglichkeiten der Bilanzierung von Humankapital - Thommes, Kirsten

Incentives to invest in the human capital of temporary agency workers - Schmidt, Stephanie; Thommes, Kirsten (German Journal of Human Resource Management)

Outsourcing HR functions. Development of an explanatory approach to firms'(non-existent) demand for personnel services - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (Management Revue)

Kooperation und Konkurrenz in Personaldienstleistungsbeziehungen - Bähring, Katrin; Thommes, Kirsten (Kooperation und Konkurrenz)

Outsourcing von Personalfunktionen - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (Motive und Erfahrungen im Spiegel von Experteninterviews)

Die Wirkungen des Outsourcings von Personalfunktionen - ein Überblick über Aussagen verschiedener theoretischer Ansätze - Alewell, Dorothea; Bähring, Katrin; Thommes, Kirsten (Jena: Sonderforschungsbereich)